Association of Neuroprotective Effect of Di-O-Demethylcurcumin on Aβ25–35-Induced Neurotoxicity with Suppression of NF-κB and Activation of Nrf2 - Decha Pinkaew (2018)
© 2015, Springer Science+Business Media New York. Amyloid-β peptides (Aβ), a major component of senile plaques, play an important role in the development and progression of Alzheimer’s disease. Several lines of evidence have demonstrated that Aβ-induced neuronal death is mediated by oxidative stress. The present study aimed to evaluate the potential involvement of di-O-demethylcurcumin, an analog of curcuminoid, on Aβ-induced neurotoxicity in culture neuroblastoma cells (SK-N-SH cells) through the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway and the suppression of nuclear factor-κB (NF-κB) signaling pathway and their downstream targets. The results showed that pretreatment with di-O-demethylcurcumin elevated cell viability and decreased the level of reactive oxygen species. Moreover, treatment with di-O-demethylcurcumin promoted the translocation of Nrf2 protein from the cytoplasm to the nucleus, increased the expression of Nrf2-ARE pathway-related downstream proteins including heme oxygenase (HO-1), NAD(P)H:quinone oxidoreductase 1 and glutamate-cysteine ligase catalytic subunit, and increased the activity of superoxide dismutase enzymes. On the other hand, di-O-demethylcurcumin suppressed the degradation of IκBα, translocation of the p65 subunit of NF-κB from cytoplasm to nucleus and thereby, attenuated the expression of inducible nitric oxide synthase protein and nitric oxide production. Taken together, these results suggest that neuroinflammatory effect of di-O-demethylcurcumin might potentially be due to inhibit NF-κB and activate Nrf2 signaling pathways induced by Aβ25–35.